Integrative Science Approach to Resilience: The Notre Dame Study of Health & Well-being (NDHWB). Issue 3 (3rd July 2021) - Bergeman, Cindy S.; Boker, Steven M.; Rose, Nathan; Bonanno, George A.; Seeman, Teresa
Abstract: Although many studies have unequivocally demonstrated the promise of understanding resilience to adversity and characterizing the consequences if stress is unabated, needed are dynamic theories and methods to enhance the rigor and interpretation of these assessments. From a dynamic systems perspective, the focus is not whether an individual possesses some fixed ability or unchangeable trait, but rather to understand the flexibility and responsiveness of stress regulation systems to daily hassles and adverse life events. A renewed interest in individual variability allows researchers to see trajectories of change over both short- and long-time scales to understand the developmental course. As a result, it is possible to answer questions, such as, how does the dysregulation in emotion caused by stress, to both within and between daily affect processes, relate to longitudinal trajectories (over time-scales of years) of dysfunction and disease? The overarching goal of the Notre Dame Study of Health & Well-being is to detail the types and qualities of contextual influences, in conjunction with dynamic psychobiological systems, to assess the precursors, concomitant influences and consequences of stress and resilience in the face of adversity on cognitive, health, and well-being outcomes.